PRACTICAL GUIDE TO COSTUMED INTERPRETATION - Lee, Jacqueline ([S.l.] : ROUTLEDGE, 2023)
A Practical Guide to Costumed Interpretation is just that - a book that takes you through the various stages of becoming an historical costumed interpreter. Jackie Lee has worked in this area of heritage interpretation for over twenty years and sets out what it takes to develop the persona for a character from the past. The methods she shares focus on first-person delivery of an historic character. Lee introduces the reader to two new methods she has developed that support character creation and delivery. The "three realms" highlight the importance of research and making the character believable and the "crystal ball" which enables the costumed interpreter to look into the future when the occasion demands it. The book is full of practical help on all aspects of the costumed interpreter's craft including costume making and how to prepare personally for stepping out full of confidence ready to engage visitors of all ages. A Practical Guide to Costumed Interpretation is aimed at those interested in becoming costumed interpreters as well as those who wish to develop or revise their techniques. It will also be useful for students of museum practice and heritage interpretation considering costumed interpretation as a means of on-site delivery.
Keywords: Interpretation of cultural and natural resources; Costume; Clothing and dress -- Styles